2013
DOI: 10.1002/lary.24349
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to chronic otitis media with effusion: Candidate gene single nucleotide polymorphisms

Abstract: Objective The genetic factors leading to a predisposition to otitis media are not well understood. The objective of the current study was to develop a tag-single nucleotide polymorphism (SNP) panel to determine if there is an association between candidate gene polymorphisms and the development of chronic otitis media with effusion. Study Design A 1:1 case/control design of 100 cases and 100 controls was used. The study was limited to the chronic otitis media with effusion phenotype to increase the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…Recent studies have suggested that children with the condition have a general reduced immunity [39]. This has led to the discovery of potential genes causing susceptibility to the condition [40,41]. It may be possible to use this information in future to identify those at risk and create tailored therapy toward individual patients.…”
Section: Surgical Treatmentmentioning
confidence: 96%
“…Recent studies have suggested that children with the condition have a general reduced immunity [39]. This has led to the discovery of potential genes causing susceptibility to the condition [40,41]. It may be possible to use this information in future to identify those at risk and create tailored therapy toward individual patients.…”
Section: Surgical Treatmentmentioning
confidence: 96%
“…Eight SNPs on 4 genes ( TLR4 , MUC5B , SMAD2 , SMAD4 ) showed a trend toward association ( P BEST_ADJUSTED = .625, rs10116253 on TLR4). 19 …”
Section: Discussionmentioning
confidence: 99%
“…We have determined that rs1110060 appears to affect expression of IQGAP1 in adenoids, though a larger population is needed to validate this observation. TGFβ signaling was found to upregulate expression of KIF7 which is important because the TGFβ pathway has been associated with OM in both mouse 71,73 and human studies 95,96,98 . Finally, expression of KIF7 and other HH signaling pathway members decreased after treatment with bacterial LPS.…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have found the TGFβ pathway to be important for OM risk in humans 95,96,115,98 and mice 71,72,179 . KIF7 lies within the Sonic hedgehog (SHH) pathway, which has been shown to interact with the TGFβ pathway.…”
Section: Evaluation Of Tgfβ Signaling Pathway Regulation Of Kif7mentioning
confidence: 99%
See 1 more Smart Citation